Metabolomics Responses of Pearl Oysters (Pinctada fucata martensii) Fed a Formulated Diet Indoors and Cultured With Natural Diet Outdoors - Yang, Chuangye; Hao, Ruijuan; Du, Xiaodong; Deng, Yuewen; Sun, Ruijiao; Wang, Qingheng (Frontiers in Physiology, 2018)
Natural disasters and environmental pollution are the main problems in traditional offshore cultivation. While culturing pearl oysters through industrial farming can avoid these problems, food availability in this case is limited. This study compares the metabolomics responses of pearl oysters, Pinctada fucata martensii, fed a formulated diet indoors with those of oysters cultured with natural diet outdoors by using a gas chromatography time-of-flight mass spectrometry (GC-TOF/MS)-based metabolomics approach. The animals were divided into two groups as follows: the experimental group (EG) was fed a formulated diet indoors and the control group (CG) was cultured with natural diet outdoors. After 45 days of feeding, the survival rate of EG was significantly higher than that of CG. The absolute growth rate (AGR) of the total weight of EG did not significantly differ from that of CG, but the AGRs of the shell length, shell height, and shell width of CG were significantly higher than those of EG. EG showed significantly higher amylase activities than CG, and the hexokinase and glucose-6-phosphate isomerase concentrations of the former were significantly lower than those of the latter. Metabolomics revealed 125 metabolites via mass spectrum matching with a spectral similarity value >700 in the hepatopancreas, and 48 metabolites were considered to be significantly different between groups (VIP > 1 and P < 0.05). Pathway analysis results indicated that these significantly different metabolites were involved in 34 pathways. Further integrated key metabolic pathway analysis showed that, compared with CG, EG had lower capabilities for cysteine and methionine metabolism, sulfur metabolism, and starch and sucrose metabolism. This study demonstrated that the formulated diet could be an excellent substitute for natural diet; however, its nutrients were insufficient. Effective strategies should be developed to enhance the utilization of formulated diets.